PENGARUH MODEL PAIRED STORYTELLING TERHADAP KETERAMPILAN BERCERITA PADA MATA PELAJARAN BAHASA INDONESIA SISWA SEKOLAH DASAR - Seha, Muhamad Nurul; Robandi, Babang; Somantri, Mubarok (Faculty of Educational Sciences,Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2024)
This research was motivated by students' lack of knowledge regarding cultural diversity in Indonesia. This research is motivated by the learning outcomes of students on cultural diversity material that needs to be improved. This study aims to determine the effectiveness of using the Cultural Diversity Interactive Card (KIBU) media in improving the learning outcomes of phase C students on cultural diversity material in Indonesia. This study used pretest and posttest instruments as many twenty multiple-choice questions in each class. This study used a quantitative research model with a Quasi-Experimental research design. The sample of this study was phase C students in one of the elementary schools in Bandung City with a sample of 52 students. The collected data was processed using IBM SPSS Statistics 26 version. The results of this study obtained data on the difference in improving student learning outcomes between the experimental class and the control class. The average result increased by 38.46 in the experimental class, and 9.61 in the control class. In the experimental class, the average N-Gain value was 73.67 and showed an increase in the high category and in the control class of 16.57 with the low category. Therefore, the use of KIBU media is declared effective in improving student learning outcomes on cultural diversity material in Indonesia.